PENGARUH PENDEKATAN KONTEKSTUAL BERBANTUAN JARIMATIKA TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS DAN KETERAMPILAN BERHITUNG SISWA PADA MATERI PERKALIAN - Hardiyanti, Sri; Maulana, M.; Julia, J. (Jurnal Pena Ilmiah, 2017)
The ability of mathematical comprehension and counting skills of students is an important aspect that needs understood by students in mathematics learning in elementary school. The aim of this research is to find out the improvement of mathematical comprehension ability and counting skills of students who get learning with contextual approaches, studying contextual approaches, and studying conventional approaches to the study of physiology. This research method is quasi experiment with data collection technique using pretest and posttest. The samples of this study were the second grade of SDN 1 Tangkil, SDN 3 Kedongdong, and SDN 1 Wiyong, and then based on the results of the different test of the sample were bound and identified that the three classes could improve the ability of mathematical comprehension and counting skills. Based on the average test of the average free sample using H-test (Kruskal-Wallis), it is known that there is a difference in the average ability of mathematical comprehension and counting skills in the three experimental classes, and it can also be known the relationship between mathematical comprehension ability and student counting skills.